The Impact of Protection on the Evolution of the Portuguese Pattern of Trade: 1974-86 - Courakis, Anthony S. (2019)
The aim in this paper is to examine the effects of trade policies on the pattern of Portuguese manufacturing trade in the years 1974/86. The beginning of this period is marked by the 1974 Revolution, the loss of colonies, and the immediate aftermath of the first oil crisis shock, while the end is defined by the first year of Portugal's membership of the EEC. The paper comprises two main sections. Section 1 presents an overview of the patterns of protection pertaining to different sub-periods of the period under review, while in section 2 we examine econometrically the contribution of such policies in accounting for the trade performance of the Portuguese manufacturing industry.